The Profitability of Indonesian Sharia Commercial Banks : Macro and Micro Economic’s Effect - Tiarawati, Tika Dewi; Putri, Rizky Nur Ayuningtyas (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2024)
Financial performance is one measure of the success of Islamic banks in managing their operations well in order to obtain maximum profitability. This research aims to determine the influence of macroeconomic factors, namely Gross Domestic Product (GDP) and inflation. The influence of microeconomic factors, namely Non Performing Financing (NPF), Capital Adequecy Ratio (CAR), Financing to Deposit Ratio (FDR) on the profitability of Sharia Commercial Banks in 2018-2022. The sampling technique was purposive sampling and nine samples of Sharia Commercial Banks were obtained which were used in this research. Secondary data in this research was obtained from each bank's financial report data, Gross Domestic Product (GDP) data was sourced from the Ministry of Trade website, and inflation data was sourced from the Bank Indonesia website. The data analysis technique is a multiple linear regression analysis technique with data processing using the Eviews 10 application. Based on the partial test, the results show that Gross Domestic Product (GDP) has no effect on ROA, inflation has no effect on ROA, Capital Adequecy Ratio (CAR) has no effect on ROA, and Financing to Deposit Ratio (FDR) has no effect on ROA. Meanwhile, partially Non Performing Financing (NPF) has an effect on ROA. Simultaneously the variables Gross Domestic Product (GDP), inflation, Capital Adequecy Ratio (CAR), Financing to Deposit Ratio (FDR), and Non Performing Financing (NPF) influence ROA.